The importance of networking as a management skill - S. De Klerk (South African Journal of Business Management, 2010)
Networking is a life skill and it is in managers' interest to acknowledge its importance and develop their own networking skills. This article reports on networking practices in Gauteng businesses. The empirical study consisted of an exploratory, sequential mixed-method research design, which included five focus group discussions (n = 41) to investigate the content of the networks and a structured questionnaire aimed at analysing the perceptions and experiences of business owners and managers in Gauteng Province in South Africa on the structure of their networks. The participants considered networking important to business success and stated that they would have benefited from training on building relationships, earlier on in their careers. Based on these findings, it is recommended that educators at all levels, managers and policy makers focus on networking as part of management training.
Keywords: 650